2019
DOI: 10.1111/1365-2656.13128
|View full text |Cite
|
Sign up to set email alerts
|

Environment‐sensitive mass changes influence breeding frequency in a capital breeding marine top predator

Abstract: The trade‐off between survival and reproduction in resource‐limited iteroparous animals can result in some individuals missing some breeding opportunities. In practice, even with the best observation regimes, deciding whether ‘missed’ years represent real pauses in breeding or failures to detect breeding can be difficult, posing problems for the estimation of individual reproductive output and overall population fecundity. We corrected fecundity estimates by determining whether breeding had occurred in skipped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…The remaining two could be relaxed through the inclusion of temporary migration. Temporary migration would permit individuals to skip breeding seasons, which is known to happen (Smout et al, 2020), or to temporarily breed at a different colony. The consequence of not incorporating this into the model is that capture probabilities are likely to underestimate the true values and as a result there may be modest effects on the estimation of recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining two could be relaxed through the inclusion of temporary migration. Temporary migration would permit individuals to skip breeding seasons, which is known to happen (Smout et al, 2020), or to temporarily breed at a different colony. The consequence of not incorporating this into the model is that capture probabilities are likely to underestimate the true values and as a result there may be modest effects on the estimation of recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an individual with capture history 1 0 0 1 1 was initially captured and marked as a pup, missed on the following two occasions (indicated by the zeros) before being resighted on the final two occasions. Resighted seals were assumed to be breeding; resight probabilities for non-breeding seals are known to be very small (Smout et al, 2020). The observed data that we will analyse consist of the capture histories for female seals tagged as pups in 1991-1994 that have been recaptured as breeding adults on the Isle of May at least once during the 1992-2011 breeding seasons.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern was seen regardless of individual differences in background energy expenditures (Figure 4). Previous work has demonstrated that female seals may adjust their reproductive output between years, when faced with changing environmental conditions prior to the lactation period, in order to maximize lifetime reproductive output (Bowen et al, 2015; Desprez et al., 2018; Kalberer, Meise, Trillmich, & Krüger, 2018; McMahon et al., 2016; Pomeroy et al., 1999; Smout et al., 2020), but research has yet to reveal the mechanism for terminating lactation in grey seals (e.g. by investigating metabolite trends leading up to weaning; Mellish & Iverson, 2001; Watson, Pomeroy, Al‐Tannak, & Kennedy, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout each breeding season, researchers surveyed the main breeding areas daily so that known seals were identified as soon as possible after coming ashore (Smout, King, & Pomeroy, 2020). When birth was not observed directly, it was estimated using age‐related mass and development characteristics (Kovacs & Lavigne, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…From late October to early December, individual females spend 18-20 days on the island, during which time they each bear and nurse one pup, enter oestrus approximately 16 days post-parturition 62 , mate, and abruptly wean their pup around day 18 of lactation 41 . The Isle of May colony was part of a long-term study of grey seal reproductive energetics and behaviour by the Sea Mammal Research Unit, SMRU 41,63 . Known individuals can be identified using pre-existing brands, flipper tags and/or pelage patterns 41,64 .…”
Section: Methodsmentioning
confidence: 99%